2004
DOI: 10.1111/j.1368-5031.2004.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary tuberculous liver abscess. A case report and review of literature

Abstract: Tuberculous liver abscess (TLA) is an extremely rare condition, even in the country where tuberculosis is an alarming public health problem. Primary TLA, with no evidence of infection elsewhere, is even less common. Herein, we report a case with primary TLA and review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Levine classified hepatic TB into various forms of presentation such as military TB, primary pulmonary TB with liver involvement, primary liver TB, tuberculoma, and tuberculous cholangitis (4). A low tissue oxygen level render the liver inhospitable for tubercular bacilli; hence the result in low prevalence of tubercular liver abscess.This presentation in an immuno-competent host needs a high level of suspicion for diagnosis (5). It can easily be confused with amebic or pyogenic liver abscess and thus leads to failure of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Levine classified hepatic TB into various forms of presentation such as military TB, primary pulmonary TB with liver involvement, primary liver TB, tuberculoma, and tuberculous cholangitis (4). A low tissue oxygen level render the liver inhospitable for tubercular bacilli; hence the result in low prevalence of tubercular liver abscess.This presentation in an immuno-competent host needs a high level of suspicion for diagnosis (5). It can easily be confused with amebic or pyogenic liver abscess and thus leads to failure of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1 Primary hepatic tuberculosis is relatively rare depending on the epidemiologic situation (non-endemic area). 2,3 It represents 0.5–1.2% of intra-abdominal localizations. 3 In most cases, hepatic tuberculosis is of a micro-nodular form (less than 2 mm).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 It represents 0.5–1.2% of intra-abdominal localizations. 3 In most cases, hepatic tuberculosis is of a micro-nodular form (less than 2 mm). 4 The macro-nodular or pseudotumoral form, also called tuberculoma, is rare.…”
Section: Discussionmentioning
confidence: 99%
“…A study from a South African general hospital showed that liver TB contributed to 1.2 per cent of the cases of TB diagnosed. 4 Several forms of HTB are described: 5,6,7  most commonly the liver is involved as a part of disseminated or pulmonary TB;…”
Section: Discussionmentioning
confidence: 99%